2022
DOI: 10.1136/postgradmedj-2022-141724
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant onset COVID-19: predictors and outcome

Abstract: PurposeDuring COVID-19 infection, organ dysfunction such as respiratory failure tends to occur towards the second week of illness; however, in a subset, there may be rapid onset of organ dysfunction as early as symptom onset. We define fulminant onset COVID-19 as rapid onset of organ dysfunction such as acute respiratory failure, acute kidney injury, acute encephalopathy or shock within 4 days of symptom onset. Fulminant onset COVID-19 has not yet been systematically studied. We aimed to identify predictors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…We observed that the risk of acute kidney disorder reached its highest level in the second week after the initiation of COVID-19 and then gradually decreased with no significance in the fourth week. Consistent with a previous study reporting that organ dysfunction tends to occur in the second week after SARS-CoV-2 infection [ 36 ], the median time to AKI occurrence was approximately 8 to 9 d after infection, corresponding to the second week [ 37 , 38 ]. Although comparable results of the time-varying hazard effects of COVID-19 on the risk of subsequently kidney outcomes are lacking, one previous study reported similar temporal trends of COVID-19 on subsequent life-threatening secondary infections [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the risk of acute kidney disorder reached its highest level in the second week after the initiation of COVID-19 and then gradually decreased with no significance in the fourth week. Consistent with a previous study reporting that organ dysfunction tends to occur in the second week after SARS-CoV-2 infection [ 36 ], the median time to AKI occurrence was approximately 8 to 9 d after infection, corresponding to the second week [ 37 , 38 ]. Although comparable results of the time-varying hazard effects of COVID-19 on the risk of subsequently kidney outcomes are lacking, one previous study reported similar temporal trends of COVID-19 on subsequent life-threatening secondary infections [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with other studies that suggest that people who are overweight or obese are more likely to have prolonged symptoms following COVID infection [ 57 , 58 , 59 ]. However, other studies claim that factors such as hypertension, chronic kidney disease, and immunocompromised states are related [ 60 ].…”
Section: Discussionmentioning
confidence: 99%